2008
DOI: 10.1016/j.biortech.2007.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up synthesis of lipase-catalyzed palm esters in stirred-tank reactor

Abstract: Lipase-catalyzed production of palm esters by alcoholysis of palm oil with oleyl alcohol in n-hexane was performed in 2L stirred-tank reactor (STR). Investigation on the performance of reactor operation was carried out in batch mode STR with single impeller mounted on the centrally located shaft. Rushton turbine (RT) impellers provide the highest reaction yield (95.8%) at lower agitation speed as compared to AL-hydrofoil (AL-H) and 2-bladed elephant ear (EE) impellers. Homogenous enzyme particles suspension wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…The rheological property of the reaction mixture might be one of the factors that determine the selection of the reactors. Several Newtonian-like mixture compounds, such as methyl ester and palm esters, were successfully synthesized in stirred tank reactors [24,25]. For adipate ester and sugar ester synthesis, slightly high agitation speed (500-600 rpm) was need to achieved maximum yield, where it may have related to their mixing property and viscosity [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rheological property of the reaction mixture might be one of the factors that determine the selection of the reactors. Several Newtonian-like mixture compounds, such as methyl ester and palm esters, were successfully synthesized in stirred tank reactors [24,25]. For adipate ester and sugar ester synthesis, slightly high agitation speed (500-600 rpm) was need to achieved maximum yield, where it may have related to their mixing property and viscosity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several Newtonian-like mixture compounds, such as methyl ester and palm esters, were successfully synthesized in stirred tank reactors [24,25]. For adipate ester and sugar ester synthesis, slightly high agitation speed (500-600 rpm) was need to achieved maximum yield, where it may have related to their mixing property and viscosity [25]. In the case of the synthesis of sucrose ester solutions, the changes in viscosity of sucrose ester solutions in dimethyl formamide (DMF) solvent were suggested due to basis of hydrogen-bond density, ester-ester/solvent-ester interactions, and mixed partial esters production [26].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the protein reagent consisting of oligomeric protein, glycoprotein, lipid constituents and globulins plus blanking buffer were added to the 24-well assay plate. The synthetic disc, which and indicates that the model has a very high correlation [19]. In this case, the R 2 was equal to 0.866914, and this coefficient value indicated that 86.69% of the variability in the response could be explained by the model.…”
Section: Skin Irritancy Testmentioning
confidence: 87%
“…Transesterification of vegetable oils to methyl esters to be used as biodiesel is carried out industrially [1] and fatty acids are used as building blocks in many products. In a typical example, a fatty acid is esterified with a fatty alcohol to produce a wax ester [2], or the wax ester is formed in the alcoholysis of a vegetable oil with a fatty alcohol [3]. Wax esters can be used for various applications, such as coatings for wood [4] or as ingredients for cosmetics [5].…”
Section: Introductionmentioning
confidence: 99%